Evaluasi Hukum Ekonomi Syariah atas Pasar Sirkular Fast Fashion dan Perlindungan Industri Tekstil Nasional - Shofa Robbani; Tahmida Masbuchah; Duwi Alfiana; Fiki Nur Dhiya’ul Ikhsan; M Alfarid Aminuddin (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
This article evaluates the circular market practices in the fast fashion industry from the perspective of Islamic economic law and analyzes their impact on the protection of the national textile industry. The rapid development of fast fashion in Indonesia has encouraged consumptive behavior that leads to waste and environmental damage. On the other hand, the circular market through thrifting of imported used clothes is considered an environmental solution but actually threatens the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the textile sector. This research uses a qualitative method with a library research approach and normative analysis based on sharia economic law principles such as Maslahah, ‘adl, Tawazun, as well as the prohibitions of israf and gharar. The results show that fast fashion practices violate the principle of israf due to excessive consumption and massive textile waste generation, while imported thrifting violates the principles of ‘adl and al-wuḍūḥ because it creates unfair competition and contains gharar regarding product quality. This study recommends a maqashid sharia-based policy reconstruction that includes strengthening import regulations, developing local circular economies, and sharia-based sustainable consumption education. A balanced and just policy is needed to integrate environmental sustainability with the protection of the national textile industry.